2016
DOI: 10.1159/000452427
|View full text |Cite
|
Sign up to set email alerts
|

Vancomycin Trough and Acute Kidney Injury: A Large Retrospective, Cohort Study

Abstract: Background: The association between vancomycin trough (VT) and acute kidney injury (AKI) at the recommended doses remains controversial. Methods: The authors conducted a retrospective, observational cohort study of 500 adult patients who received vancomycin for ≥72 h. Data collected included 2 main predictors: average VT (including only VTs before the occurrence of AKI), first VT and other possible risk factors for AKI. The baseline characteristics/variables between patients with AKI and patients with no AKI w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 16 publications
0
18
0
Order By: Relevance
“…Another study assessing the risk of AKI with VAN/PTZ versus VAN/CEF revealed a greater risk of developing AKI with VAN doses between 3 and 4 g/day, but not with doses 4 g/day or greater (OR 1.6, CI 1.11–2.32, p=0.01, and OR 1.3, CI 0.5–3.05, p=0.6, respectively) . Steady‐state VAN trough concentrations of 15 μg/ml or greater were associated with a greater risk of developing AKI in several studies . Independent risk factors identified in other studies included dehydration, patient weight, concomitant use of acyclovir, amphotericin B, or loop diuretics, duration of VAN treatment 7 days or longer, longer duration of hospital stay, receipt of VAN loading dose, presence of two or more systemic inflammatory response syndrome criteria, and a documented gram‐positive infection …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study assessing the risk of AKI with VAN/PTZ versus VAN/CEF revealed a greater risk of developing AKI with VAN doses between 3 and 4 g/day, but not with doses 4 g/day or greater (OR 1.6, CI 1.11–2.32, p=0.01, and OR 1.3, CI 0.5–3.05, p=0.6, respectively) . Steady‐state VAN trough concentrations of 15 μg/ml or greater were associated with a greater risk of developing AKI in several studies . Independent risk factors identified in other studies included dehydration, patient weight, concomitant use of acyclovir, amphotericin B, or loop diuretics, duration of VAN treatment 7 days or longer, longer duration of hospital stay, receipt of VAN loading dose, presence of two or more systemic inflammatory response syndrome criteria, and a documented gram‐positive infection …”
Section: Discussionmentioning
confidence: 99%
“…9 Steady-state VAN trough concentrations of 15 lg/ml or greater were associated with a greater risk of developing AKI in several studies. 10,22,33,[39][40][41][42][43][44][45] Independent risk factors identified in other studies included dehydration, patient weight, concomitant use of acyclovir, amphotericin B, or loop diuretics, duration of VAN treatment 7 days or longer, longer duration of hospital stay, receipt of VAN loading dose, presence of two or more systemic inflammatory response syndrome criteria, and a documented gram-positive infection. 9,22,24,31,39 Baseline characteristics, specifically the significantly higher mean Charlson Comorbidity Index in the MER group, may indicate a higher severity of illness than those who received PTZ.…”
Section: Discussionmentioning
confidence: 99%
“… 1 , 2 The recent study confirmed that prevalence of MRSA with reduced susceptibility to VAN was gradually increased, which prompted specialists to recommend for higher target trough serum concentrations. 3 , 4 , 5 However, the use of larger doses of VAN has led to a wider report of acute kidney injury (AKI) cases. 6 , 7 Although the most of them are mild or even reversible, both the greater incidence of end-stage renal disease (ESRD) and higher mortality rate may be associated with their germination.…”
mentioning
confidence: 99%
“…Both of these mean values have a wide standard deviation and are considerably lower than the often cited 15 mg/L for prevention of vAKI. [ 12 , 21 , 32 34 ] We sought to minimize the concerns of causation versus outcome by collecting serum vancomycin concentrations in the 72 hours prior to vAKI, and to collect values at particular times after a dose, rather than a trough concentration, to capture data from those patients who may have been receiving non-scheduled vancomycin dosing due to real or perceived pre-existing kidney dysfunction. [ 20 ] Therefore, we were unable to evaluate serum concentrations at specifically at steady state, and values sampled at steady state may be different than what we have been able to capture.…”
Section: Resultsmentioning
confidence: 99%